COMMUNICATIVE ORIENTATION OF THE TEACHING PROCESS IN EFL CLASSROOM - Begizova Madina Karimovna (Academia Science Repository, 2023)
The focus of the article is developing communicative skills of EFL learners. In the article it is stressed that in the process of teaching a foreign language teachers should be governed by, at least, two principles. One is, that no matter what work is carried out in the class, it should have speech-thinking orientation. And the second one is situationality, which presupposes discussion round different true-to-life situations